Ophthalmomyiasis Case Caused by Two Blow Fly (Diptera: Calliphoridae) Species in North America - Taylor B. Parker; Kelly A. Meiklejohn; Gregory A. Dahlem; Ralph C. Eagle; Marius J. Heersink (The Scientific World Journal)
Ophthalmomyiasis is the result of fly larvae feeding on the tissues of the eye. Commonly associated with poor hygiene and open wounds, this condition is rare and often stigmatized. Treatment can be straightforward, and full recovery is common. Identifying the species responsible for ophthalmomyiasis is important for the medical, forensic, and entomological communities. Here, we present a case of ophthalmomyiasis where 30–40 blow fly (Diptera: Calliphoridae) larvae were removed from the eye of a human male. A representative subsample of five larvae was used for taxonomic identification via two approaches (a) DNA analysis, via sequencing of the complete mitochondrial genome (mtGenome) and comparison of the mtGenome and mitochondrial COI barcode region to GenBank, and (b) morphology, examination of the posterior spiracles using microscopy, and comparison to published larval descriptions of blow flies. Two species of blow flies were identified from the DNA analysis: Lucilia coeruleiviridis and Phormia regina. Morphological examination could only confirm L. coeruleiviridis as being present. To our knowledge, finding two blow fly species causing ophthalmomyiasis in a single individual has not been previously reported in the scientific literature. Neither P. regina nor L. coeruleiviridis prefers living tissue for larva development, but since they fill similar ecological niches, perhaps this was a show of competition rather than a normal feeding habit. Knowing these blow fly species can resort to this behavior, and that it can affect human populations, is valuable to the education of patients and providers.